2014
DOI: 10.1128/jvi.02278-13
|View full text |Cite
|
Sign up to set email alerts
|

Structural Stability of Influenza A(H1N1)pdm09 Virus Hemagglutinins

Abstract: IMPORTANCEHemagglutinins from the early 2009 H1N1 pandemic viruses are unable to maintain a trimeric complex when expressed in a recombinant system. However, HAs from 2010 and 2011 strains are more stable, and our work highlights that the improvement in stability can be attributed to an E374K substitution in the HA2 subunit of the stalk that emerged naturally in the circulating viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 31 publications
1
57
0
Order By: Relevance
“…However, we found that M2 enhanced HA-mediated cell-cell fusion when HA was cleaved by either HAT or TPCK-trypsin, indicating that M2-mediated enhancement of fusion is not specifically due to HAT expression. Importantly, (H1N1)pdm09 HA is known to be less stable than many other human influenza virus H1 HA proteins (19)(20)(21). Our data therefore suggest that M2 protects (H1N1)pdm09 HA from undergoing some degree of pH-induced conformational change that impairs its function even prior to cleavage into mature HA.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, we found that M2 enhanced HA-mediated cell-cell fusion when HA was cleaved by either HAT or TPCK-trypsin, indicating that M2-mediated enhancement of fusion is not specifically due to HAT expression. Importantly, (H1N1)pdm09 HA is known to be less stable than many other human influenza virus H1 HA proteins (19)(20)(21). Our data therefore suggest that M2 protects (H1N1)pdm09 HA from undergoing some degree of pH-induced conformational change that impairs its function even prior to cleavage into mature HA.…”
Section: Discussionmentioning
confidence: 66%
“…This finding indicates that M2 protects (H1N1)pdm09 HA from premature conformational changes during HA transport to the cell surface. Because (H1N1)pdm09 HA is less stable than many other H1N1 HA proteins (19)(20)(21), our data suggest that M2 proton channel activity may be especially important for HA proteins that are less stable, regardless of subtype or cleavage site motif.…”
mentioning
confidence: 89%
“…Residue 84 of seal11 NA was mutated (Asn84Gln) to remove the potential glycosylation site (NNT to QNT). Secreted proteins were recovered from the culture supernatant and purified by metal affinity chromatography and size exclusion chromatography (SEC) as described previously (29,(32)(33)(34)(35). For structural analyses, the proteins were further subjected to trypsin cleavage and SEC.…”
Section: Methodsmentioning
confidence: 99%
“…The HA from the pandemic 2009 H1N1 influenza A virus [A(H1N1)pdm09] has been reported to be less stable than the HAs of other seasonal influenza A virus strains (28)(29)(30)(31), a feature that likely contributes to challenges in the production of A(H1N1)pdm09 vaccines (28,29). Moreover, it was recently reported that the currently circulating A(H1N1)pdm09 virus is acquiring mutations that improve HA stability (31,32) and may therefore improve viral fitness.…”
Section: Influenza Virus Hemagglutinin (Ha) Is the Principal Antigen mentioning
confidence: 99%